Relationship between R&D grants, R&D investment, and innovation performance: The moderating effect of absorptive capacity. Issue 1 (19th June 2019) - Zhu, Hailun; Zhao, Shuliang; Abbas, Asad
Abstract : The main sources of regional innovation investment in China are government direct investment and indirect grant. The positive relationship between innovation investment and regional innovation performance has been recognized by scholars, but the relationship between direct investment, indirect grant, and innovation performance and the mechanism of their impact on innovation performance need to be clarified. This study uses 5‐year data from China regional innovation, using multiple regression analysis, found that government grant and actor's investment can facilitate performance, but the government grant for innovation investment has a crowding‐out effect, absorptive capacity positively moderated the relationship between Research and Development (R&D) and innovation performance but play a negative moderate role between government grant and innovation performance. On the basis of the empirical result, China's regional governments need to focus on institutional and environmental development in the future, pay more attention to the structural problems of innovation input, promote flow of talents orderly, and rationally build regional knowledge chain, so as to enhance efficiency of innovation more effectively.